The Covert Surge: Murine Bile Acid Levels Are Associated With Pruritus in Pediatric Autoimmune Sclerosing Cholangitis - Katharina Meinel; Doloresz Szabo; Antal Dezsofi; Sina Pohl; Tanja Strini; Theresa Greimel; Victor Aguiriano-Moser; Harald Haidl; Martin Wagner; Axel Schlagenhauf; Jörg Jahnel (Frontiers Media S.A., 2022)
ObjectivesThe exact etiology of pruritus in chronic cholestasis is unknown. Pruritus intensity does not correlate with common biochemical indices and there is a lack of biomarkers guiding diagnosis and treatment. We explored profiles of bile acids (BA) and muricholic acids (MCA) as well as autotaxin (ATX) antigen levels as potential circulating biomarkers of pruritus in pediatric patients.MethodsIn 27 pediatric cholestatic patients [autoimmune sclerosing cholangitis (ASC) n = 20 (with pruritus n = 6, without pruritus n = 14); progressive familial intrahepatic cholestasis (PFIC) n = 7 (with pruritus n = 5, without pruritus n = 2)] and 23 age-matched controls pruritus was assessed by a visual analog scale of pruritus (PVAS). We obtained profiles of serum human BA including MCA using a mass-spectrometry assay and ATX antigen levels with a commercial ELISA.ResultsPFIC and ASC patients exhibited significantly higher BA-, and MCA levels, than healthy controls, but only PFIC patients showed elevated ATX antigen levels higher [median: 1,650 ng/ml, interquartile rang (IQR): 776.9-3,742] compared to controls (median: 315.9 ng/ml, IQR: 251.1-417.2; PFIC p = 0.0003). ASC patients with pruritus showed only a minor increase in total BA (tBA) levels (median: 76.5 μmol/L, IQR: 54.7-205), but strikingly higher T-conjugated BA (median: 16.4 μmol/L, IQR: 8.9-41.4) and total MCA (tMCA) (median: 1.15 μmol/L, IQR: 0.77-2.44) levels compared to ASC patients without pruritus (tBA median: 24.3 μmol/L, IQR: 16.2-80.8; p < 0.0408; T-conjugated BA median: 1.3 μmol/L, IQR: 0.8-4.9; p = 0.0023; tMCA median: 0.30 μmol/L, IQR: 0.13-0.64, p = 0.0033). BA/MCA profiles distinctly differed depending on presence/absence of pruritus. Different from PFIC patients, ATX antigen levels were not significantly elevated in ASC patients with (median: 665.8 ng/ml, IQR: 357.8-1,203) and without pruritus (median: 391.0 ng/ml, IQR: 283.2-485.6). In ASC patients, tBA, tMCA, and ATX antigen levels did not correlate with pruritus severity.ConclusionDespite the same underlying disease, pediatric ASC patients with pruritus exhibit significantly altered BA profiles and MCA levels compared to ASC patients without pruritus. ATX antigen levels seem to have little diagnostic or prognostic meaning in ASC patients. An increased ATX activity alone seems not to be causal for pruritus genesis in ASC patients.Clinical Trial Registration[www.drks.de], identifier [DRKS00026913].